2020
DOI: 10.13057/biodiv/d211212
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antagonistic Streptomyces strains isolated from Algerian Saharan soils and their plant growth promoting properties

Abstract: Abstract. Aouar L, Boukelloul I, Benadjila A. 2020. Identification of antagonistic Streptomyces strains isolated from Algerian Saharan soils and their plant growth promoting properties. Biodiversitas 21: 5672-5683. To produce new bioactive substances of agricultural interest, extreme ecosystems can be a source of unexplored microorganisms. Accordingly, in this study, twenty-two actinobacteria strains were obtained from rhizospheric arid soils of palm groves collected from Biskra and El Oued in the Algerian Sah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 57 publications
(89 reference statements)
4
9
0
Order By: Relevance
“…The locations of the three explored sites are: site-1 /Chaiba (34°78'20''N, 5°04'97''E), site-2 /Chegga (34°45'19''N, 5°89'18''E) and site-3 /El Feidh, (34°46'15''N, 6°57'06''E). From each site, the root systems of Atriplex halimus L. (roots and soil surrounding the halophyte) were taken from the soil and gently scraped to separate rhizospheric soil, remove debris (roots and stones) and collect about 100-150 g. The soil samples were then filled into sterile container and transported to the laboratory for analysis (Aouar et al, 2020).…”
Section: Study Site Soil Samples Collection and Their Physico-chemica...mentioning
confidence: 99%
See 2 more Smart Citations
“…The locations of the three explored sites are: site-1 /Chaiba (34°78'20''N, 5°04'97''E), site-2 /Chegga (34°45'19''N, 5°89'18''E) and site-3 /El Feidh, (34°46'15''N, 6°57'06''E). From each site, the root systems of Atriplex halimus L. (roots and soil surrounding the halophyte) were taken from the soil and gently scraped to separate rhizospheric soil, remove debris (roots and stones) and collect about 100-150 g. The soil samples were then filled into sterile container and transported to the laboratory for analysis (Aouar et al, 2020).…”
Section: Study Site Soil Samples Collection and Their Physico-chemica...mentioning
confidence: 99%
“…In addition to fungal damage, bacteria are responsible for 24% of the 14% overall yield damage engendered by phytopathogens, including S. scabies, P. carotovorum, Agrobacterium tumefaciens, Erwinia amylovora and Xanthomonas spp. (Aouar et al, 2020;Le et al, 2022). Common radish scab disease is caused by several Streptomyces spp., mainly induced by S. scabies, it does not affect yield, but it badly impacts marketability (Kang et al, 2022).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…played an important role in inhibiting the growth and density of G. boninense. Actinomycetes are also known to suppress the growth of other soil-borne pathogens such as V. dahliae, F. oxysporum, B. cinerea, R. solani, and A. flavus (Aouar et al 2020).…”
Section: Actinomycetes Isolatesmentioning
confidence: 99%
“…For micro-biotic variables, the richness of the microbial community and keystone OTU4911 (S. eurythermus) and OTU4672 (S. flaveus) significantly affect the distribution of plants. Streptomyces, isolated from Algerian Saharan soil, produces indole-3-acetic acid and siderophores, which dissolve phosphate, promote plant growth, and have antimicrobial properties against phytopathogenic bacteria (AOUAR et al, 2020). Previous studies have shown that Streptomyces in the arid soils of Antarctica are predicted to encode antitumour, antifungal, antibacterial and biosurfactant-like compounds (Benaud et al, 2021).…”
Section: Topography Precipitation and Soil Bacteria Drive The Coloniz...mentioning
confidence: 99%